Using machine learning for measuring democracy: An update - Klaus Gründler; Tommy Krieger (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We provide a comprehensive overview of the literature on the measurement of democracy and present an extensive update of the Machine Learning indicator of Gründler and Krieger (2016, European Journal of Political Economy). Four improvements are particularly notable: First, we produce a continuous and a dichotomous version of the Machine Learning democracy indicator. Second, we calculate intervals that reflect the degree of measurement uncertainty. Third, we refine the conceptualization of the Machine Learning Index. Finally, we largely expand the data coverage by providing democracy indicators for 186 countries in the period from 1919 to 2019.
Keywords: C38; C43; C82; E02; P16; 330; Data aggregation; Democracy indicators; Machine Learning; Measurement Issues; Regime Classifications; Support Vector Machines